Effects of immersion media and repolishing on color stability and superficial morphology of nanofilled composite resin - Oliveira, Ana Luísa Botta Martins de [UNESP]; Botta, Ana Carolina; Campos, Juliana Alvares Duarte Bonini [UNESP]; Garcia, Patrícia Petromilli Nordi Sasso [UNESP] (Oxford University Press (OUP), 2014)
This study evaluated the influence of fluoride mouth rinses and repolishing on the superficial morphology and color stability of nanofilled resin. About 150 specimens were prepared and polished using aluminum oxide discs for 15 s with a pressure of 2 kg. The experimental groups were divided according to the immersion medium (artificial saliva, 0.5% sodium fluoride, Fluordent Reach, Oral B, Fluorgard) and repolishing procedure (without and with). The specimens were continuously immersed for 1 week. Thereafter, half of each sample was repolished. A color reading was performed after 24 h of immersion in the artificial saliva baseline, after continuous immersion, and after repolishing. The superficial morphology was examined using scanning electron microscopy (SEM) in a qualitative way. Color change (∆E) data were submitted to a mixed analysis of variance using a Shapiro-Wilk test (p>0.05 for the different immersion media) and Sidak's test (p<0.05 for the differences between groups). In the interaction between the repolishing and the immersion media, Fluorgard showed a statistical difference between the ∆E values with and without repolishing (p<0.0001). On the SEM observations, both Fluordent Reach and Fluorgard caused degradation of the superficial resinous matrix of the composite after continuous immersion. This matrix was removed after repolishing.
Keywords: Fluorine; Composite resins; Color; Dental polishing; SEM; Microscopy; Repolimento; Alteração de cor; Resina composta; Flúor